All‐in‐One Process for Color Tuning and Patterning of Perovskite Quantum Dot Light‐Emitting Diodes. Issue 13 (1st March 2022) - Kim, Junho; Seo, Ki‐Won; Lee, SeungJae; Kim, Kyungmin; Kim, Changjo; Lee, Jung‐Yong
Abstract: Although post‐synthetic anion exchange allows halide perovskite quantum dots to easily change the optical bandgap of materials, additional exchange of shorter ligands is required to use them as active materials in optoelectronic devices. In this study, a novel all‐in‐one process exchanging ligands and halide anions in film‐state for facile color tuning and patterning of cesium lead halide perovskite colloidal quantum dot (PeQD) light‐emitting diodes (LEDs) is proposed. The proposed all‐in‐one process significantly enhances the performances of PeQD LEDs by passivating the PeQD with shorter ligands. In addition, the all‐in‐one process is repeated more stably in the film state. Red, green, and blue LEDs with extremely narrow emission spectra using cesium lead bromide PeQDs and appropriate butylammonium halide solutions are fabricated. Furthermore, the proposed all‐in‐one process in film‐state facilitated rapid color change in localized areas, thereby aiding in realizing fine patterns of narrow widths (300 µm) using simple contact masks. Consequently, various paint‐over red/green/blue patterns in PeQD LEDs by applying halide solutions additively are fabricated. Abstract : A novel all‐in‐one process with simultaneous ligand and anion exchange for cesium lead halide perovskite quantum dot (PeQD) light‐emitting diodes (LEDs) is proposed. Through the all‐in‐one process, it can enhance the PeQD LED performance and easily convert the emitting light color. Furthermore, the various patterned LEDs without direct exposure of ultraviolet ray or electron‐beam to PeQD layer can be realized.